2021
DOI: 10.48175/ijarsct-839
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Monster: A Great Challenge for The Youth

Abstract: In this rapidly changing advents of science and technology, Social Media has captured and ensnared young and old, rich and poor, male and female, east and west across the globe. Social networking sites like Facebook, MySpace, Skype, YouTube are gaining popularity with pace of time and due to their attractive features the youth of today is fascinated towards them. On the contrary, the seamy side of social media consistently inflicting its adverse effect, the youth tends to distract themselves from their study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…
Recent studies of social media use among Indian university students have found that the vast majority of users spend more than two hours per day on these sites. Yadav and Yadav (2017) conducted research on the use of WhatsApp among Indian youth and found that the majority of users accessed the platform for social rather than work reasons. More study is needed to fully understand the effects of digital communication on the social lives of young adults in India, as shown by the findings of these studies.
…”
mentioning
confidence: 99%
“…
Recent studies of social media use among Indian university students have found that the vast majority of users spend more than two hours per day on these sites. Yadav and Yadav (2017) conducted research on the use of WhatsApp among Indian youth and found that the majority of users accessed the platform for social rather than work reasons. More study is needed to fully understand the effects of digital communication on the social lives of young adults in India, as shown by the findings of these studies.
…”
mentioning
confidence: 99%